The Mastery of Teacher Emotional Intelligence Facing 21st Century Learning - Defrianti, Denny; Iskandar, Iskandar (Yayasan Nurul Yakin Bunga Tanjung, 2022)
21st century learning is marked by the era of digital disruption that requires teachers who have high skills through mastering emotional intelligence to prepare superior and competitive students. The purpose of this study was to determine how the emotional intelligence mastery of teachers in 21st century learning. This study used mixed methods with explanatory models. The data collection instrument used a questionnaire and interview guidelines. The data collected were analyzed by quantitative and qualitative descriptive. The research respondents were teachers in Jambi province who attended the training 20 people and those who did not attend the training 20 people with a total of 40 people. Sample selection was done by purposive sampling technique. The results showed that the average emotional intelligence of teachers was high with the average score of the intelligence of teachers attending training with a mean score of 83.30 and teachers without training with a mean score of 78.02. Furthermore, the emotional intelligence of teachers who are trained significantly affects 21st century learning which dominantly uses technology with the homogeneity test results of 0.333 with a Sig value. 0.020 where t count > 0.05, while for the t test, the t-test value is < 0.05. However, in the learning process, teachers still find it difficult to integrate the use of technology so that high psychological pressure causes self-awareness and self-control to be less stable so that teachers find it difficult to determine the appropriate learning model to use.